Chinese-Russian Collaboration: The Ice Road in the Arctic - CASIS-Vancouver (The Journal of Intelligence, Conflict, and Warfare, 2018)
On March 22, 2018, the Canadian Association for Security and Intelligence Studies Vancouver hosted its second roundtable meeting themed by a presentation on “The Arctic Dimensions of China’s Belt and Road Initiative” by Dr. Eva Busza, Vice-President of the Asia Pacific Foundation. The following question period and roundtable discussion gave a number of perspectives on the security implications of both this Belt and Road Initiative (BRI), as well as the controversy surrounding recent revelations about Cambridge Analytica’s data collection.